Origins and Implications of a Primary Crown-of-Thorns Starfish Outbreak in the Southern Great Barrier Reef. (26th March 2015) - Miller, Ian; Sweatman, Hugh; Cheal, Alistair; Emslie, Mike; Johns, Kerryn; Jonker, Michelle; Osborne, Kate
Abstract : The crown-of-thorns starfish (COTS) is a major predator of hard corals. Repeated COTS outbreaks in the Cairns and Central sections of the Great Barrier Reef (GBR) have been responsible for greater declines in coral cover than any other type of disturbance, including cyclones, disease, and coral bleaching. Knowledge of the precise timing and location of primary outbreaks could reveal the initial drivers of outbreaks and so could indicate possible management measures. In the central GBR, COTS outbreaks appear to follow major flooding events, but despite many years of observations, no primary outbreak has ever been unequivocally identified in the central and northern GBR. Here we locate a primary outbreak of COTS on the southern GBR which is not correlated with flooding. Instead it appears to have been the result of a combination of life history traits of COTS and prevailing oceanographic conditions. The hydrodynamic setting implies that the outbreak could disperse larvae to other reefs in the region.